The role of ophthalmology departments in overcoming health care disparities - Salowe, Rebecca J. (J Epidemiol Res, 2016)
Ophthalmology departments can play a unique role in providing care for at-risk patients. This study analyzed the age, gender, and socioeconomic measures for 267,286 unique African American patients seen at University of Pennsylvania Health System (UPHS). Patients seen by the Ophthalmology Department (n=33,801) were older and more likely to be from impoverished zip codes than those seen by other UPHS specialists. These results hint at several inherent advantages of ophthalmology departments in recruiting older, disadvantaged patients to their clinics. We found that supplementing this advantage with strong patient relationships, involvement of community leaders, and customized outreach efforts was key to overcoming access-to-care issues and to reaching these patients. This provides ophthalmologists with a unique opportunity to capture and refer systemic conditions with ocular manifestations and to possibly reduce disparities such as post-hospitalization readmission and mortality observed disproportionately in impoverished populations.